2003
DOI: 10.1046/j.1365-313x.2003.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis ABORTED MICROSPORES (AMS) gene encodes a MYC class transcription factor

Abstract: SummaryVisual screening of a T-DNA mutagenised population of Arabidopsis thaliana for an absence of silique elongation lead to the isolation of the aborted microspores (ams) mutant that shows a sporophytic recessive male sterile phenotype. Homozygous mutant plants are completely devoid of mature pollen. Pollen degeneration occurs shortly after release of the microspores from the tetrad, prior to pollen mitosis I. Premature tapetum and microspore degeneration are the primary defects caused by this lesion, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
367
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(385 citation statements)
references
References 49 publications
(51 reference statements)
13
367
1
4
Order By: Relevance
“…Identification of putative orthologs in different species will benefit the study of gene function, such as AtMYC2 (Abe et al, 2003) and OsMYC (Zhu et al, 2005), AMS (AtbHLH021; Sorensen et al, 2003) Zhang, unpublished data). The identity and similarity of their full-length sequences were about 32% and 42%, respectively, and 70% and 76% within the two bHLH domains.…”
Section: The Expression Pattern Of Osbhlh and Atbhlh Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of putative orthologs in different species will benefit the study of gene function, such as AtMYC2 (Abe et al, 2003) and OsMYC (Zhu et al, 2005), AMS (AtbHLH021; Sorensen et al, 2003) Zhang, unpublished data). The identity and similarity of their full-length sequences were about 32% and 42%, respectively, and 70% and 76% within the two bHLH domains.…”
Section: The Expression Pattern Of Osbhlh and Atbhlh Genesmentioning
confidence: 99%
“…The identity and similarity of their full-length sequences were about 32% and 42%, respectively, and 70% and 76% within the two bHLH domains. AMS is critical for tapetal cell differentiation and likely regulates a postmeiotic transcriptional program supporting microspore development (Sorensen et al, 2003). Similar to ams, loss of function of TDR seems to result in delayed tapetal cell degradation and causes complete male sterility.…”
Section: The Expression Pattern Of Osbhlh and Atbhlh Genesmentioning
confidence: 99%
“…Expression patterns similar to that of At1g27710 have been described for several other regulators of microsporogenesis that are essential for normal pollen formation. These genes included ABORTED MICROSPORES (At2g16910; Sorensen et al, 2003), MALE MEIOCYTE DEATH1 (At1g66170), MYB80 (At5g56110; Li et al, 1999;Stracke et al, 2001), and MS2 (At3g11980; Aarts et al, 1997). As for At2g42940 and At1g27710, we found that most of these genes also showed a prolonged expression in ms1 mutant flowers (Fig.…”
Section: Validation Of Predicted Expression Patternsmentioning
confidence: 99%
“…Genetic analyses have led to the isolation of several mutants with distinct defects in stamen development (Dawson et al, 1993;Sanders et al, 1999;Schiefthaler et al, 1999;Yang et al, 1999;Canales et al, 2002;Zhao et al, 2002;Reddy et al, 2003;Sorensen et al, 2003;Steiner-Lange et al, 2003;Albrecht et al, 2005). Cloning of the genes affected in these mutants resulted in the identification of key regulators of stamen formation.…”
mentioning
confidence: 99%
“…Tapetal cell development and differentiation are critical for the early events in male reproduction, including meiosis; however, during late pollen development, tapetal degeneration, triggered by an apoptosis-like process, is also vital for viable pollen formation (Papini et al, 1999;Varnier et al, 2005;Li et al, 2006;Aya et al, 2009). Currently, although several genes encoding putative transcription factors have been reported to be associated with tapetal function and degeneration, such as Arabidopsis (Arabidopsis thaliana) MYB33/MYB65 (Millar and Gubler, 2005), DYSFUNCTIONAL TAPETUM1 (DYT1; Zhang et al, 2006), ABORTED MICROSPORE (AMS; Sorensen et al, 2003;Xu et al, 2010), and MALE STERILITY1 (MS1; Wilson et al, 2001;Ito and Shinozaki, 2002) and rice (Oryza sativa) GAMYB (Kaneko et al, 2004;Aya et al, 2009;Liu et al, 2010), UNDEVELOPED TAPETUM1 (UDT1; Jung et al, 2005), TAPETUM DE-GENERATION RETARDATION (TDR; Li et al, 2006), and MADS3 (Hu et al, 2011), their detailed functional roles in regulating tapetal PCD during anther development are unclear. We have shown that the Arabidopsis ms1 mutant displays altered tapetal development, with a lack of normal PCD and abnormal tapetal degeneration associated with large autophagic vacuoles and mitochondrial swelling (Vizcay-Barrena and Wilson, 2006).…”
mentioning
confidence: 99%